2004
DOI: 10.1243/0957650041761946
|View full text |Cite
|
Sign up to set email alerts
|

Effective gas-to-gas heat exchanger by means of energy conversion between gas enthalpy and thermal radiation

Abstract: This paper presents the heat transfer characteristics of a new type of gas-to-gas heat exchanger that operates on the basis of energy conversion between gas enthalpy and thermal radiation. A theoretical analysis is conducted for the one-dimensional system where convection and radiation take place simultaneously in three porous layers. In the high-temperature section, the enthalpy of gas flow converts to thermal radiation and the reverse direction of this process occurs in two recovery sections. The porous medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It is clarified from these experiments that the optical thickness of about eight is enough to obtain sufficient total HR. For the purpose of improving the heat exchanger efficiency, Gandjalikhan Nassab [9] proposed a self-insulated type of gas-to-gas heat exchanger with a three-layered structure. He found that the optical thickness and scattering albedo are the main design parameters for this type of heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…It is clarified from these experiments that the optical thickness of about eight is enough to obtain sufficient total HR. For the purpose of improving the heat exchanger efficiency, Gandjalikhan Nassab [9] proposed a self-insulated type of gas-to-gas heat exchanger with a three-layered structure. He found that the optical thickness and scattering albedo are the main design parameters for this type of heat exchanger.…”
Section: Introductionmentioning
confidence: 99%